If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -13 + 3 = x + 1 Reorder the terms: -13 + 3 + 2x = x + 1 Combine like terms: -13 + 3 = -10 -10 + 2x = x + 1 Reorder the terms: -10 + 2x = 1 + x Solving -10 + 2x = 1 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -10 + 2x + -1x = 1 + x + -1x Combine like terms: 2x + -1x = 1x -10 + 1x = 1 + x + -1x Combine like terms: x + -1x = 0 -10 + 1x = 1 + 0 -10 + 1x = 1 Add '10' to each side of the equation. -10 + 10 + 1x = 1 + 10 Combine like terms: -10 + 10 = 0 0 + 1x = 1 + 10 1x = 1 + 10 Combine like terms: 1 + 10 = 11 1x = 11 Divide each side by '1'. x = 11 Simplifying x = 11
| 710c-10=2/5 | | 4x-1=x+4 | | 2p^2+2=-28 | | 7x^2+20x-10=0 | | 5x+20x-3y=4x+7 | | 4k^2-8=320 | | 20*(12-4.8)=30*4.8 | | 34b+5=14 | | 5x+4y=-2x+10y | | 5t-2=11t+5 | | 3x^2-10=200 | | =5y-1 | | 6x-2(2x+9)=34 | | 5x-3x=8x+4 | | f(x)=6x/10-x | | 10+25m^2=110 | | X^3=x^2-4x+4 | | 5x+10x+2=7x+10 | | 7x+1=6x+4 | | 6m^2n/24mn | | 10-5x=(20-10x)1/2 | | 2x=27-1 | | h(x)=7x^2-3 | | 4cos(pi/4) | | 6x^3-9x^2-6x=0 | | r(x)=3(1.4)x | | c=2pi*5 | | 44-12w=-3 | | 0=12w-47 | | (6x-4)-(2x+8)= | | 20=12+2x | | f(-2)=4x^2-8x+3 |